Dividend Taxes and Decisions of MNEs: Evidence from a Finnish Tax Reform - Jarkko Harju; Seppo Kari (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this study we explore how a firm-level dividend tax on redistributed foreign profits affects the financial decisions of a multinational enterprise (MNE). We examine this by using evidence from a recent tax reform in Finland. The so-called equalization tax (EQT) used to be a regular element of European imputation systems, designed to ensure that dividends were not paid out of untaxed profits. Theoretical analyses have suggested that EQT may distort several financial decisions of MNEs. We find a 23 percent increase in dividend payments and a similar increase in repatriated foreign profits after the repeal of EQT among Finnish MNEs. We also find evidence that the reported profits increased among foreign subsidiaries of Finnish MNEs, which indicates an effect on profit-shifting. No change in investment was detected.
Keywords: H25; F23; H32; 330; taxation; multinational firms; firm behavior